2016
DOI: 10.1111/jcpt.12368
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of metabolic monitoring for psychiatry inpatients treated with second-generation antipsychotics utilizing a computer-based intervention

Abstract: The rate of metabolic monitoring for inpatients on SGA therapy did not significantly change over time with the continued use of the CPOE pop-up alert. Optimal monitoring utilizing a CPOE pop-up alert may allow the psychiatry team, including psychiatric pharmacists, to better manage metabolic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 8 publications
0
26
0
1
Order By: Relevance
“…The majority of these (n = 25) were quantitative, 4 were qualitative [73][74][75][76] and 4 of a mixed methods [77][78][79][80] study design. Twenty of these studies included a study intervention where quantitative outcome data allowed for impact to be assessed-statistical tests of significance of data obtained for outcome parameters reported by study authors (a pre-post study design (n = 14)) or they compared groups where study intervention was implemented against group where the study intervention was not implemented (a case-control study design (n = 5) [78,79,[81][82][83] or randomised controlled study (n = 1) [84]. Table 3 shows that the most common setting for study intervention was a community mental health/psychiatric outpatient clinic (n = 15), followed by psychiatric inpatient wards (n = 12).…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of these (n = 25) were quantitative, 4 were qualitative [73][74][75][76] and 4 of a mixed methods [77][78][79][80] study design. Twenty of these studies included a study intervention where quantitative outcome data allowed for impact to be assessed-statistical tests of significance of data obtained for outcome parameters reported by study authors (a pre-post study design (n = 14)) or they compared groups where study intervention was implemented against group where the study intervention was not implemented (a case-control study design (n = 5) [78,79,[81][82][83] or randomised controlled study (n = 1) [84]. Table 3 shows that the most common setting for study intervention was a community mental health/psychiatric outpatient clinic (n = 15), followed by psychiatric inpatient wards (n = 12).…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 99%
“…One study was based in early intervention/psychosis services [86] and one based in other (mix of urban, non-urban and metropolitan centres) [71,72]. Pharmacists were involved to some extent in delivering the interventions across all studies, and those involved were mostly commonly specialist mental health/psychiatric pharmacists (n = 9) [73,79,83,[85][86][87][88][89][90] or clinical pharmacists (n = 9) [76,78,81,82,[91][92][93][94][95] (Table 4). Differences in terminology across studies due to differences in country of origin did not allow us to differentiate grades or qualification of pharmacists.…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 99%
“…One study found nearly 30% of inpatients prescribed at least one SGA met criteria for metabolic syndrome 7 . In 2004, to address risks of increased metabolic adverse effects, the American Diabetes Association (ADA) and the American Psychiatric Association (APA) released a set of guidelines on metabolic monitoring in patients taking SGAs, which have not been widely implemented in psychiatric settings 8,9 . Since the release of these guidelines, steps have been taken to increase the monitoring of these laboratory (lab) values.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…Despite the well-documented association between serious mental illness and increased risk of diabetes and cardiovascular disease, studies consistently demonstrate poor health screening and monitoring in this group of patients. 20,21 A systematic review and meta-analysis of pooled data from 5 countries, involving 218,940 patients with severe mental illness at baseline and 71,594 patients after guideline introduction, concluded that metabolic monitoring rates for patients with mental illness on antipsychotic medication were low. 20 The only parameters where rates of routine monitoring exceeded 50% were measurement of blood pressure and triglyceride levels.…”
Section: Monitoring Cardiovascular Health and Metabolic Syndrome In Imentioning
confidence: 99%
“…Computerised systems have been shown to improve patient monitoring. 21 This should be complemented with effective collaboration between mental health and primary care services to promote integrated care. 25…”
Section: Monitoring Cardiovascular Health and Metabolic Syndrome In Imentioning
confidence: 99%